Sakha Music: Selling 'Exotic' Europeanness in Asia and Asianness in Europe - Aimar Ventsel (Sciendo, 2014)
In this paper I compare strategies to sell Sakha music in different countries over a ten-year period with a particular emphasis on 2005–2007. due the fact that local income from performing and selling albums is not sufficient for living the artists from the republic of Sakha are trying to perform as much abroad as possible. When touring abroad, the music and performances have changed over time depending on the region. Sakha artists attempt to respond to the expectations of the audience and modify their program accordingly. In a period from the late 1990s to 2007, the same artists have switched from pop to rock to folk music, using different languages and different costumes, performing as Asian or European artists. comparing these strategies, one can see how Sakha musicians use cultural stereotypes of foreign audiences for economic purposes.